Assessment of Interleukin-35 and Interleukin-17 Levels in Women with Trichomonas vaginalis: A Cross-Sectional Study in Baghdad, Iraq - Al-Mothafer, Sahar M. A. (American Journal of Biology and Natural Sciences, 2026)
Trichomoniasis vaginalis infection, a prevalent infectious disease which is not viral and a sexually transmitted disease, has a tremendous impact on women's reproductive health, pro-inflammatories Interleukin-17 (IL-17) and a regulatory cytokine Interleukin-35 (IL-35) is the key to determining the course of disease. The present study aimed at quantifying serum levels of IL-35 and IL-17 between women with T. vaginalis infection and normal counterparts living in Baghdad, Iraq, and compare the possible correlation between these two important cytokines. This is a cross section study done in Baghdad. 120 women with microbiologically confirmed infection of T. vaginalis and 120 age matched healthy controls were enrolled. Serum IL-17 and IL-35 level assay was performed by a standardized enzyme immunoassay. Statistical analyses were done and the threshold for significance was determined to be p< 0.05. The infected group showed significantly high levels of serum IL-17 production (45.71±9.93 pg/mL) as compared to control group (15.80±5.10 pg/mL; p< 0.001). Contrary to this, the IL-35 level was considered significantly reduced in patients (20.32±6.97 pg/mL) when compared to controls (38.78±11.52 pg/mL; p <.001). Moreover, a statistically significant inverse relationship between IL-17 and IL-35 in infected subjects was found (r=-0.42, p<0.001). The data indicates that there is a severe immunological imbalance in women who have been born in Baghdad with an infection of Trichomonas vaginalis and is characterized by an imbalanced pro-inflammatory response of IL-17 and at the same time a suppressions of the regulatory IL-35 pathway.